The Influence of Perceived Usefulness, Ease of Use, Attitude, Self-efficacy, and Subjective Norms Toward Intention to Use Online Shopping - Shabrina Ramadania; Zaki Braridwan (International Business and Accounting Research Journal, 2019)
Technology development in this era has promoted new innovation in shopping. Nowadays, there are a popular trading forms called online shopping system. Online shopping can become a new medium for buyers and sellers to do a transaction in goods or services. In Indonesia, online shopping has become popular nowadays. This research examines the factors influencing consumers to use online shopping. In this study, the author uses quantitative research method. The data collection method uses questionnaires. The respondents are 300 active undergraduate students from accounting department at the University of Brawijaya. The research data and hypothesis are analyzed using linear regression based on partial least squares (PLS). These research findings indicate that intention to use online shopping is determined by perceived usefulness, ease of use, attitude, self-efficacy, and subjective norms. All those variables have a positive influence towards an intention to use online shopping. It can be concluded that the higher perceived usefulness, ease of use, attitude, self-efficacy, and subjective norms, the higher the effect toward intention to use online shopping.